The Influence of Work Environment and Workload on Nurses’ Performance in Inpatient Care Units - Bianti Putri Sekarani; Farida Yuliaty; Etty Sofia Mariati Asnar; Ayu Laili Rahmiyati; Vip Paramarta (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Improving the quality of hospital services is strongly associated with the performance of nurses, who play a vital role in delivering patient care and ensuring organizational effectiveness. Nurses’ performance is influenced by various factors, particularly the work environment and workload. A supportive work environment can enhance motivation, job satisfaction, and productivity, while a balanced workload enables nurses to perform their duties efficiently and maintain high standards of care. This study aimed to analyze the effects of the work environment and workload on the performance of nurses in the inpatient unit of Royal Prima Jambi Hospital, both individually and simultaneously. A quantitative research design was employed, involving 48 nurses selected as study participants. Data were collected through structured questionnaires and analyzed using multiple linear regression techniques. The findings revealed that both the work environment (X1) and workload (X2) had a positive and statistically significant effect on nurses’ performance (Y). These results indicate that improvements in workplace conditions and effective workload management contribute substantially to enhanced nursing performance. Furthermore, the coefficient of determination (R²) was 0.721, demonstrating that 72.1% of the variation in nurses’ performance could be explained by the combined influence of the work environment and workload, while the remaining 27.9% was attributable to other factors not examined in this study. The study highlights the importance of creating a conducive work environment and implementing appropriate workload allocation strategies to optimize nurses’ performance and improve the overall quality of healthcare services. These findings provide valuable insights for hospital management in developing policies aimed at strengthening workforce performance and service quality.